Concise Reviews: Stem Cells and Kidney Regeneration: An Update - Marcheque, Julia (Stem Cells Transl Med, 2018)
Significant progress has been made to advance stem cell products as potential therapies for kidney diseases: various kinds of stem cells can restore renal function in preclinical models of acute and chronic kidney injury. Nonetheless this literature contains contradictory results, and for this reason, we focus this review on reasons for apparent discrepancies in the literature, because they contribute to difficulty in translating renal regenerative therapies. Differences in methodologies used to derive and culture stem cells, even those from the same source, in addition to the lack of standardized renal disease animal models (both acute and chronic), are important considerations underlying contradictory results in the literature. We propose that harmonized rigorous protocols for characterization, handling, and delivery of stem cells in vivo could significantly advance the field, and present details of some suggested approaches to foster translation in the field of renal regeneration. Our goal is to encourage coordination of methodologies (standardization) and long‐lasting collaborations to improve protocols and models to lead to reproducible, interpretable, high‐quality preclinical data. This approach will certainly increase our chance to 1 day offer stem cell therapeutic options for patients with all‐too‐common renal diseases. Stem Cells Translational Medicine 2019;8:82–92